Codigestão anaeróbia de vinhaça e efluente secundário de laticínio em reator UASB: potencial metanogênico e dinâmica microbiana envolvida - Siqueira, Juliano Curi de (2022)
Brazil is one of the countries that has most invested in producing biofuels worldwide, standing out in ethanol production from sugarcane processing. In addition to bioethanol, this activity also generates unintended by-products such as vinasse, which is commonly used for fertigation. However, its inadequate application on agricultural soil may cause negative environmental impacts, and its treatment before final disposal is recommended. For instance, anaerobic digestion is an alternative for the treatment of this wastewater in order to reduce its polluting potential and recover its chemical energy through CH4 yield. Nevertheless, due to its unfavorable physical and chemical properties, the in natura vinasse can inhibit the anaerobic microorganisms and stop the treatment process. Therefore, strategies to enable vinasse biodegradation are required. In this regard, the present study evaluated the performance of the anaerobic co-digestion of sugarcane vinasse and secondary effluent from the dairy industry (mixture 1:1 v/v) in a lab-scale upflow anaerobic sludge blanket (UASB) reactor (16 L). The reactor operated for 91 days at room temperature (26 °C on average), with alkalinity control (0.3 gNaHCO3 gCOD-1), an influent flow rate of 3.6 L d-1, a hydraulic retention time of 4.44 d, and an average organic loading rate of 1.6 kgCOD m-3 d-1. As an inoculum for the system, anaerobic biomass from a municipal sewage treatment plant was selected based on comparative tests of specific methanogenic activity (SMA). The respective recorded average and maximum pollutant removals were: total chemical oxygen demand (69% and 81%), acidity (29% and 53%), volatile (51% and 75%) and total (48% and 69%) suspended solids, ammoniacal (6% and 100%) and total Kjeldahl (42% and 73%) nitrogen, total phosphorus (19% and 69%), total potassium (0% and 4%), phenols (51% and 77%), and sulfates (25% and 67%). Moreover, the average and maximum methane yields were 221 and 308 mLCH4 gCODrem-1, respectively. The biogas produced had average volumetric contents of 66.47% CH4, 11.43% CO2, and 53 ppm H2S. Furthermore, the present study demonstrated the periodic evolution of the microbial community contained in the sludge of the evaluated system, from the inoculation to the end of the operation, both in terms of microorganism identification through sequencing by synthesis and by performing SMA assays. At the end of the operation, there was an increase in the relative abundance of the phylum Euryarchaeota (+8.6% compared to the inoculum), with a predominance of hydrogenotrophic methanogenic archaea (Methanobacterium and Methanobrevibacter genera). In parallel, an increase in SMA was observed over the operation. These results demonstrate a gradual adaptation of the anaerobic microbiota to the substrate. In summary, it is concluded that the proposed co-digestion resulted in a stable and efficient anaerobic treatment, thus allowing satisfactory levels of pollutant removal and methane production. It is recommended in future studies to conduct experiments on the vinasse anaerobic treatability by adopting different operational strategies in bioreactors, aiming at both a greater energy recovery and a more significant reduction of the polluting potential of the effluent.